Current Practices on Prescribing and Deprescribing for Patients on Long-Term Antibiotic Treatment for Chronic Pulmonary Conditions: An Umbrella Review by the European Society of Clinical Pharmacy (ESCP) - Tadic, Ivana; Fialová, Daniela; Hazen, Ankie; C Henman, Martin; Okuyan, Betul; Wirth, Francesca; Abdi, Abdikarim; Urru, Silvana; R Stover, Kayla; E Weidmann, Anita (COPD, 2025)
PURPOSE: Chronic pulmonary conditions require complex treatment strategies involving long-term antibiotic treatment, which carries the highest risk of antimicrobial resistance and adverse drug events (ADE). Specific guidance on prescribing and deprescribing can help reduce these risks and improve therapy effectiveness. The aim of the study was to determine prescribing and deprescribing practices for long-term antibiotic treatment (≥30 days) in preventing exacerbations of stable chronic pulmonary conditions in adult patients across all healthcare settings. PATIENTS AND METHODS: This umbrella review was part of a larger registered study (PROSPERO, CRD42022381268) including systematic reviews and meta-analyses retrieved from PubMed, Cochrane Library, and PsycInfo. Outcomes of interest included condition, antibiotic, dose, duration, (de-) prescribing advice. Standardized methodological tools were used to assess methodological quality of the selected publications (ROBIS), facilitate data extraction (EPOC), and guide narrative summary of findings (PRIOR). RESULTS: In total, n = 14 publications were analyzed. (De-)prescribing advice is summarized for treatment (≥30 days) of chronic obstructive pulmonary disease, asthma, non-cystic fibrosis bronchiectasis, cystic fibrosis, and bronchiolitis obliterans syndrome. Macrolides are the most commonly recommended antibiotic for stable chronic pulmonary conditions. ADEs are the main reason for antibiotic discontinuation. Little consideration is given to emergence of antibiotic resistance. CONCLUSION: There is a significant paucity of literature providing specific (de-)prescribing advice for clinical practice. More precise recommendations are required in view of patient safety.
Keywords: Bronchiectasis; lékařská praxe - způsoby provádění; bronchiolitis obliterans syndrome; Lung Diseases; non-cystic fibrosis bronchiectasis; systematický přehled jako téma; asthma; cystická fibróza; lidé; Anti-Bacterial Agents; Pulmonary Disease, Chronic Obstructive; Asthma; depreskripce; antibiotics; bronchiektazie; chronická obstrukční plicní nemoc; Systematic Reviews as Topic; Chronic obstructive pulmonary disease; bronchiální astma; Cystic Fibrosis; Meta-Analysis as Topic; chronická nemoc; Deprescriptions; antibakteriální látky; plicní nemoci; Chronic Disease; lung diseases; metaanalýza jako téma; Practice Patterns, Physicians'; Humans